Clinical management of foot rot in goats: a case report of lameness - Bitrus, Asinamai Athliamai; Abba, Yusuf; Abdullah, Faez Firdaus Jesse; Lim, Mei Yi; Robinn, Teoh; Sadiq, Muhammad Abubakar; Lim, Eric Teik Chung; Mohd Lila, Mohd Azmi; Haron, Abd Wahid (Network for the Veterinarians of Bangladesh, 2017)
Objective: Foot rot is one of the most important causes of lameness and economic losses in sheep and goats world-wide. This case report described the clinical management of lameness due to foot rot in two female Boer goats aging 4-year both from two different farms in Selangor, Malaysia. Materials and methods: The goats were presented with the complaint of non-weight bearing lameness of the right forelimbs. The hoof was broken and the interdigital space was filled with dirt and exuding a foul smelling odor. Results: On clinical examination, the goats were looking as dull and isolated with body condition scores of 2.5/5 (case 1) and 3/5 (case 2), respectively. The goats had a rectal temperature of 38.8°C and 40.4°C, pulse rate of 80 and 100 beats per minutes, and respiratory rate of 44 and 24 cycles per minute, respectively. Blood sample was collected for complete blood count and serum biochemistry from case 1 only. The hoof was thoroughly washed and disinfected. Parenteral administrations of Flunixin meglumine (dosed at 2.2 mg/kg bwt, IM) thrice daily and Oxytetracycline (dosed at 20 mg/kg bwt, IM case 1) once and Sulfadiazine+trimethoprim (dosed at 1 mL/16 kg bwt, IM case 2) for 3 days. Topical oxytetracycline was applied to the area for 5 days. Conclusion: The prognosis was very good as there was a significant improvement in the hoof injury of both animals. The goats were recovered after 7 days of treatment.